Murphy house - Kjysten Drew:::Creator::::::::::::
Murphy house. 402 Cayuga Street, Salinas, CA. The Murphys were family friends of the Steinbecks. Dr Murphy saved Steinbeck's life in 1917 by draining his pneumonic lung. Dr Murphy made an appearance in East of Eden as the doctor who tends to Adam after Adam's stroke. Original is slide.